A methods engineering study of GTI Sportswear Corporation - Dimaculangan, Eric; Llaguno, Erickson L.; Padilla, Ferdinand S. (Diliman, Quezon City College of Engineering, 1994)
Productivity and efficiency are major concern of any business enterprise. Thus, this study focused on methods improvement by which productivity is hoped to be increased. General improvements were also touched with regards to lay-out and on working conditions. Operations with high rejection rates were identified and analyzed. Specifically, two operations which the group were equipped to deal with, were selected. The Ishikawa diagram detailing possible causes of production rush, was also presented and discussed. The study on systems and procedures focused on the analysis of the company's administrative workflow, record management program and the design and control of forms. Some additional information for the forms were proposed. Likewise, the organizational set-up was revised such that two apparent separate functions performed by two groups were combined, since in actuality they are done by just one group of people. The group recommends further studies on some of the recommendations that may involve capital outlay.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: GTI Sportswear Corporation; Sport clothes industry; Systems analysis